The optimal design of pensions and financial education, when individuals are biased and naive - Chiara Canta; Marie-Louise Leroux (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2022)
This paper studies the optimal design of a pension system together with publicly-provided individualized financial education. Agents can invest in both a risky and a non risky asset and can either under- or over-estimate the expected return of the risky asset. We show that, under perfect information on the misperception biases, it is optimal for the government to impose a uniform level of pension contributions equal to the first-best level of investment in the nonrisky asset and a U-shaped level of education. Under asymmetric information, we show that the level of education is always distorted upward for agents with important misperception biases (who either under- or over-estimate financial returns) but, can be distorted upward or downward for agents with mild misperception biases. Whether we end up in one or the other situation depends on the size of the public and private costs of education as well as on the shape of the distribution of the misperception biases in the economy.
Keywords: D14; H21; H53; H55; I22; 330; Pension systems; financial education; misperception; taxation; asymmetric information